Mesenchymal stromal cells for the treatment of Alzheimer’s disease: Strategies and limitations - Regmi, Shobha; Liu, Daniel Dan; Shen, Michelle; Kevadiya, Bhavesh D.; Ganguly, Abantika; Primavera, Rosita; Chetty, Shashank; Yarani, Reza; Thakor, Avnesh S. (Frontiers in Molecular Neuroscience, 2022)
Alzheimer’s disease (AD) is a major cause of age-related dementia and is characterized by progressive brain damage that gradually destroys memory and the ability to learn, which ultimately leads to the decline of a patient’s ability to perform daily activities. Although some of the pharmacological treatments of AD are available for symptomatic relief, they are not able to limit the progression of AD and have several side effects. Mesenchymal stem/stromal cells (MSCs) could be a potential therapeutic option for treating AD due to their immunomodulatory, anti-inflammatory, regenerative, antioxidant, anti-apoptotic, and neuroprotective effects. MSCs not only secret neuroprotective and anti-inflammatory factors to promote the survival of neurons, but they also transfer functional mitochondria and miRNAs to boost their bioenergetic profile as well as improve microglial clearance of accumulated protein aggregates. This review focuses on different clinical and preclinical studies using MSC as a therapy for treating AD, their outcomes, limitations and the strategies to potentiate their clinical translation.